Analysis of the SDS-PAGE patterns of outer membrane proteins from Escherichia coli strains that have lost the ability to form K1 antigen and varied in the susceptibility to normal human serum - Cisowska, Agnieszka; Bugla-Płoskońska, Gabriela (Folia microbiologica, 2014)
We used SDS-polyacrylamide gel electrophoresis to investigate the outer membrane proteins (OMPs) band composition of 19 Escherichia coli K1 strains that have spontaneously lost the ability to form K1 polysaccharide capsule (E. coli K1-) and demonstrated different degrees of susceptibility to the bactericidal action of normal human serum. Presented results showed that there were differences between E. coli K1- strains in OMPs expressing capacity. The analysis performed on OMPs has not revealed a direct association between the different OMPs band composition and the susceptibility of these strains to the serum.
Keywords: bakteriální pouzdra; Polysaccharides, Bacterial; Electrophoresis, Polyacrylamide Gel; Escherichia coli Infections; infekce vyvolané Escherichia coli; antigeny bakteriální; proteiny vnější bakteriální membrány; baktericidní aktivita krve; Escherichia coli; mikrobiální viabilita; Bacterial Outer Membrane Proteins; lidé; bakteriální polysacharidy; Bacterial Capsules; Urinary Tract Infections; Microbial Viability; Antigens, Bacterial; infekce močového ústrojí; Blood Bactericidal Activity; elektroforéza v polyakrylamidovém gelu; Humans